Does intellectual capital determine the firm's investment efficiency? Evidence from Indonesia - Khasanah, Siskha Nur; Hwa, Pan Wei; Hakim, Muhammad Saiful (Dinasti Publisher, 2024)
Companies now recognize that success depends not only on physical assets but also on effectively utilizing intangible assets like intellectual capital to outperform competitors. In other hand, achieving the most effective investment decisions is a core concern in corporate finance and a primary objective for management in a company. However, uncertainty of outcome and a lack of measurement metrics often lead to inefficient investments. This study intends to assess the relationship between intellectual capital (IC) on investment efficiency (IE). The data is processed using panel data regression on non-financial public companies in Indonesia with an observation period of 2010-2023. Our analysis discovered that the human capital (HCE) of a firm statistically has a significant positive impact on investment efficiency. Second, the capital component (CEE) is negatively affecting investment efficiency. At the same time, no relationship was found between structural capital and investment efficiency.